Contribution of a Novel Pertussis Toxin-Like Factor in Mediating Persistent Otitis Media - Ma, Longhuan; Sedney, Colleen; Su, Yang; Dewan, Kalyan K.; Linz, Bodo; Harvill, Eric T. (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic otitis media (COM) is the long-term infection and inflammation of the middle ears typically caused by upper respiratory tract pathogens that are able to ascend the Eustachian tube. Our understanding of contributing factors is limited because human otopathogens cannot naturally colonize or persist in the middle ears of mice. We recently described a natural COM in mice caused by Bordetella pseudohinzii and proposed this as an experimental system to study bacterial mechanisms of immune evasion that allow persistent infection of the middle ear. Here we describe a novel pertussis toxin (PTx)-like factor unique to B. pseudohinzii, apparently acquired horizontally, that is associated with its particularly efficient persistence and pathogenesis. The catalytic subunit of this toxin, PsxA, has conserved catalytic sites and substantial predicted structural homology to pertussis toxin catalytic subunit PtxA. Deletion of the gene predicted to encode the catalytic subunit, psxA, resulted in a significant decrease in persistence in the middle ears. The defect was not observed in mice lacking T cells, indicating that PsxA is necessary for persistence only when T cells are present. These results demonstrate the role of a novel putative toxin in the persistence of B. pseudohinzii and its generation of COM. This PsxA-mediated immune evasion strategy may similarly be utilized by human otopathogens, via other PTx-like toxins or alternative mechanisms to disrupt critical T cell functions necessary to clear bacteria from the middle ear. This work demonstrates that this experimental system can allow for the detailed study of general strategies and specific mechanisms that otopathogens use to evade host immune responses to persist in the middle ear to cause COM.